Climate Investment Plan for the Agriculture Sector: A Decision Support Tool for Scaling up Climate-Smart Agriculture Technologies and Practices in Gandaki Province, Nepal - Neupane, Santosh; Khatri, Laxman; Bhusal, Aastha; Neupane, Ghrishma; Shivakoti, Sabnam (2021)
Gandaki Province is centrally located in Nepal with most of its area being hills and high hills (64%). There are 11 districts in Gandaki Province with one metropolitan city, namely, Pokhara; 26 municipalities and 58 rural municipalities. Gandaki Province contributes about 9% to the GDP of the whole country. In terms of agriculture production, Gandaki Province is food deficit and relies on other provinces for the supply of pulses, fruits, vegetables, and livestock products. Of the total area of the province, 24% of the land area is cultivable; around 24% of the cultivable land is fallow land (117,076 ha), which remains a great challenge for the upcoming days in terms of food production and enabling food security in the province. The prevalent climate is varied in the province starting from the plains of Nawalpur to the high Himalayas of Manang and Mustang. The highest maximum temperature has been recorded in Kaski district (30.7°c) and lowest minimum temperature has been recorded in Manang district (-4.6°c) over the time period 1971 to 2014. Similarly, the highest annual precipitation has been recorded in Kaski district (2,710.5 mm) while the lowest annual precipitation has been recorded in Mustang district (257.8 mm). Varied climatic risks are prevalent in Gandaki Province such as temperature and rainfall risk, ecological risk, flood, landslide, drought and Glacier Lake Outburst Flood (GLOF) risk. Lamjung district is very highly prone to the combined risk index of all these risks. Similarly, Gorkha, Tanahun, Manang, Myagdi, Parbat and Baglung districts are highly prone to the combined risk index. The Nepalese economy is highly dependent on the agriculture and forestry sector which contributes around 33% of the national GDP. Agriculture is climate sensitive, which makes the Nepalese economy vulnerable to climatic variability. Although Nepal is one of the most vulnerable countries in the world to erratic climate phenomenon, Nepal’s contribution to greenhouse emissions is negligible. Food production and food security are of high concern in the changing climatic scenario as compared to land availability at individual household level. In the Nepalese context, food security is of high importance; despite the fact that agriculture is still subsistence in nature. Food production in these changing climatic/socio-economic situation and people’s access to food are the key indicators of food security. Thus, adoption of CSA technologies at farmers’ field level is of immense importance in order to mitigate the ill effects of climate change while ensuring food production and food security. The Climate Investment Plan (CIP) has been designed as a decision-making tool for agricultural investment in terms of adoption of climate smart agricultural (CSA) technologies. It will act as a yard stick to the government and policy makers to calculate how much investment is needed for attaining certain levels of crop production, thereby enhancing the livelihood of the farming society. Adoption of CSA technologies is expected to improve food production, increase agricultural income, increase technical efficiency of inputs used, enhance climate change adaptation, and produce a low environmental footprint. With the changing weather conditions, decreased farm production and productivity it is of prime necessity to enhance crop/livestock production in the Nepalese context. Adoption of CSA technologies by farming communities is the most appropriate way to do this. CIP will act as a document to guide government authorities to plan, implement, monitor and evaluate agricultural investment targeted to enhance agricultural/livestock production via adoption of CSA technologies. The Climate Investment Plan has been methodologically divided into five steps: The first two steps consist of the formation of a climate risk matrix and risk-CSA matrix. The climate risk matrix was formed at district level to identify climatic risks pertaining to individual crop/livestock. Similarly, the risk-CSA matrix contains the potential CSA technologies addressing the climate risk for each crop/livestock at district level. These two steps help in the identification of climate risk pertaining to each crop/livestock commodity and potential CSA options. Thirdly, cost of cultivation was calculated for normal production and along with CSA technologies with the help of experts. This data was analyzed using Excel Solver in the fourth step and climate investment was carried out in the fifth step. Crop specific CSA technologies were selected from Excel Solver analysis, an Excel based commonly used optimization technique, and a certain area was allocated for cultivation which in general maximized the production/income while minimizing GHG emissions and human labour use in agricultural operations. Individual CSA technologies in each crop/livestock component was treated as a single treatment i.e., no bundling of technologies. Each CSA technology were treated as a single component while looking at the production, productivity and income generation. In the case of rice, a system of rice intensification (SRI), alternate waiting and drying (AWD), improved varieties, effective nutrient management, direct seeded rice (DSR), use of farm yard manure (FYM), and normal rice cultivation were the CSA technologies recommended/identified from the expert’s consultation (representing NARC, DoA and MoALD). Similarly, in wheat production, ICT, minimum tillage, improved varieties, nutrient management and normal production systems were identified. Likewise, different CSA technologies were identified for maize, lentil, black gram, potato, tomato, cole crops, apple, banana, mango, sweet orange, and mandarin orange. In the case of livestock - cow, buffalo, goat and fish were selected and cost benefit was analyzed. Due to lack of cost of production data for these livestock components from government sources, experts in their respective fields were used for the purpose. Gandaki Province needs to invest in seed, fertilizer, mulching materials, pesticide and micronutrients as required for crop commodity production. Investment in building infrastructure i.e., irrigation facilities, can be a long term investment by the provincial government. Similarly, crop/livestock insurance schemes should be a yearly strategic programme in the province. The Climate Adaptation Investment Plan has been developed mainly after considering the input supply needed while adopting the CSA technologies. Provincial government is recommended to provide a 25%, 15% and 5% subsidy on the input cost for the first three years of implementing the plan. From the 4th year onwards, the provincial government should make proper arrangements for collateral/interest free loan to the farming communities via proper channels. The investment amount has been calculated based on CSA technology and districts selected for each crop items. Crop and district specific (selected districts) investment should be done to augment agricultural production/productivity in the province. For livestock production, we lack official data on cost and return and the estimates done in this report are based on experts’ judgement and knowledge. Unlike crops/fruits/vegetables, CSA technologies are very specific in the case of livestock production. In the case of buffalo milk production, high yielding breeds in both the Terai and hill regions are expected to give higher returns from the investment. Similarly, for cow milk, high yielding breeds are expected to give higher return on the investment. Regarding goat farming, high yielding goat breeds need to be introduced in the Nepalese situation to make goat farming a lucrative agri-business. Fish farming can be promoted to make Nepalese fish production enough to feed the population. Rainbow trout is best suited to the cold running water in the hill regions of Nepal. Similarly, polyculture of Carps, Catfish, Pangas and other fish can be produced across both the Terai and hill regions. As the present study is based on secondary data sources and experts’ consultation, the results generated from this study are prone to errors but maximum diligence has been given to make the results more authentic and pragmatic. The investment portfolio generated in this study is based on CSA technologies that are/can be relevant to Gandaki Province. No socio-economic and gender perspective study has been carried out to validate the CSA technologies at farmer level. The present study has generated investment at district/ province pertaining to specific crop commodities. Authentic data from credible sources is required at municipal/rural-municipal/ward level to estimate the investment required at these levels.